Minimal channel between microcomputers and peripherals (CAMIC). - Rodriguez Espinoza, M.; Rodriguez Rossini, G. (Revista Mexicana de Ingenieria Biomedica, 1988)
In a dedicated control microcomputer, the high degree of integration of the elements around the microprocessors facilitates the solution of instrumentation problems, since the entire system can be divided into two parts; the microcomputer itself and the direct peripherals with the application. From this arises the need to have an appropriate means of communication between them, so this work is presented as a means of communication between microcomputers and peripherals. Showing the results obtained from this channel.